Copper Homeostasis in Aspergillus fumigatus: Opportunities for Therapeutic Development - Song, Jinxing; Li, Rongpeng; Jiang, Jihong (Frontiers in Microbiology, 2019)
Aspergillus fumigatus can cause severe invasive aspergillosis in immunocompromised individuals. Copper, an essential but potentially toxic trace element for A. fumigatus, plays a critical role at the host-pathogen axis during infection. Accumulating evidence demonstrates that the host utilizes copper compartmentalization within macrophages to combat A. fumigatus infection. To survive under host-imposed copper toxicity, A. fumigatus has evolved sophisticated machinery to regulate copper homeostasis. Thus, targeting molecular pathways critical for copper homeostasis regulation provides an opportunity to improve therapeutic options for aspergillosis caused by A. fumigatus. In this review, we describe the copper homeostatic mechanisms by which A. fumigatus acquires and controls copper levels and explore the responses of the pathogen to altered copper levels in the host. Finally, we discuss the regulatory mechanisms of copper homeostasis that could be targeted for antifungal drug development